(untitled) (Research, Society and Development, 2023)
The objective of this research is to describe the use of information and communication technologies (ICT) in the construction of knowledge in geography at the State School Prof.ª Bernardete Socorro Trindade da Rocha with students from two classes of the 5th grade of elementary school. The purpose research methodology was classified as applied science, as the objective of the study was labeled as exploratory, the analysis of results occurred qualitatively and quantitatively. The period of practical application took place in August 2021. The universe of the research was a teacher and 60 students of the 5th year of elementary school, the place of study was at the Bernadete Socorro Trindade State School. The analysis unit was 60 elementary school students and one teacher. In the end, it is understood that the use of Google Earth presented itself satisfactorily, not only for the process of significant learning of the student, besides offering educators a tool for the development of teaching practice, in view of the methodological proposal. Although socioeconomic status seems to be postulated as a determining factor with the greatest impact on students’ educational outcomes, a broader and more in-depth analysis of studies addressing this phenomenon shows that the school trajectory is the result of the combination of multiple factors located in the individual, family, school and community spheres.